Community Engagement in Implementing Education Policies to Improve Learning Quality in Remote Areas - Ali Yusron (Didaktika: Jurnal Kependidikan, 2025)
The quality of learning in remote areas faces various challenges due to limited access, resources, and socioeconomic dynamics. This study aims to examine the role of community involvement in the implementation of education policies to improve the quality of learning in remote areas. With a qualitative case study approach, data was collected through in-depth interviews, observations, and documentation from 30 participants consisting of teachers, principals, parents, community leaders, and local government officials. The results showed that 83% of the community was actively involved in the process of planning, implementing, and evaluating education policies, with real contributions in the form of the formation of study groups and the provision of additional learning facilities. This increase in engagement correlates with a 12% increase in student academic scores over the past two years. However, obstacles in the form of internal conflicts and limited economic resources still hinder the optimization of participation. These findings strengthen the theory of social participation and social capital in the context of education and show the success of a more systematic model of community participation compared to previous studies. The practical implications of this study emphasize the importance of inclusive and collaborative strategies that empower communities as key partners in the development of education in remote areas.